STRATEGI PEMASARAN UMKM LEDYS CAKE PADA ERA DIGITAL DI KOTA TANJUNGPINANG - Ledysta Faradila Putri; Salsabila Salsabila; Yusrillah Yusrillah; Muhammad Firmansyah (Universitas Kristen Indonesia Toraja, 2022)
Technological developments and increasingly high business competition make MSME actors must have a good marketing strategy to be able to compete with their competitors. This research was conducted to determine the marketing strategy carried out by Ledys Cake SMEs in facing competition in the digital era. The research method in this study uses a qualitative approach through structured interviews with business actors. The results of the study show that MSMEs provide added value and differentiation to the products and services provided, while in terms of price, they apply competitive prices. The application of technology is more widely used in culinary businesses through websites and social media to establish good relationships and communicate with consumers. The researcher concludes that there are several discussions, namely Strategy, Constraints and Solutions. The strategy carried out by MSMEs is that there is a 4P (Product, Promotion, Price, Place) mix. Product strategy in the form of innovation, promotion strategy in the form of price discounts, price strategy for every purchase of cake will get a bonus, and place strategy in the form of flexibility in sending cake orders, so as to maintain and improve the quality of the taste of the cake. Although there are financial constraints and product raw materials, we can still find solutions and alternatives, namely by managing finances and using raw materials efficiently. Then, MSME solutions by maintaining cash flow, product innovation, maximizing social media and delivery services